Tephra from Primary and Rootless Cones from the 1.9 ka Nesjahraun Eruption, Þingvellir, SW Iceland: A Comparison - Tapscott, Sarah, 1992- (2018)
The overall architecture of primary and rootless cones is similar in many respects and therefore differentiation can be challenging. In this thesis, I compare microtextural properties of primary and rootless cone tephra from the 1.9 ka Nesjahraun eruption to investigate the physical properties that allow for robust distinctions between the two volcanic constructs. Previous studies on the microtextural properties of rootless eruption tephra are limited and therefore this type of a study is an ideal avenue to further the knowledge on these multifaceted volcanic formations. The Nesjahraun eruption features both tephra types and thus ideal for comparing the microtextural properties of their tephra clasts. Results show that the primary vent tephra is characterised by narrow, low density distributions. It features coalesced, oval to polygonal shaped vesicle population and an order of magnitude higher vesicle number densities than the rootless cone tephra. These characteristics are attributed to relatively rapid magma ascent during which the decoupling of melt and bubbles resulted in vesicle coalescence. Conversely, the rootless cone tephra is characterised by broad, high density distributions and exhibits a clast vesicularity that is lower than the primary cone tephra by an approximate factor of two. Vesicles are oval to spherical in shape and show minimal evidence of coalescence. The vesicle populations of the rootless cone tephra suggest that the vesicles nucleated and grew during molten fuel-coolant interactions, either due to temporary supersaturation of magmatic volatiles or incorporation of external water into the molten magma.